THE INFLUENCE OF INSECTICIDES ON PEROXIDASE AND POLYPHENOLOXIDASE ENZYME ACTIVITY IN LEAVES OF POTATO PLANTS - Крижко, А. В.; Кузнєцова, Л. М. (Scientific Progress & Innovations, 2013)
It was established that the enzyme activity of peroxidase and polyphenoloxidase in potato plants leaves depends on the type of the insecticides and the term of preservation on the leaf surface. Under the bioinsecticides based on the strains B. thuringiensis 994 and 787 it has been noted an insignificant and short increase of the enzyme activity after 6-8 days after their application. It may be reasonable phytoimmunological response of plants on the preparations processing or it can evidence the plants ability to keep stable oxidative metabolism and increase the adaptive capacity of plant organism. The plants processing by the chemical insecticide Calypso do not promote the formation of nonspecific resistance in plants throughout the period of research.